Can academic librarians as data scientists revolutionise user-centric e-learning? - Sa'ari, Haziah; Goulding, Anne; Sahak, Mohd Dasuki (Academic Conferences International Ltd, 2023)
This investigation illuminates the vital contributions of academic librarians (ALs) functioning as data scientists (DSs) within the e-learning landscapes of Malaysian public universities. Derived from comprehensive interviews with ten experience ALs, this study distinguishes three key areas of contribution towards user-centric and effective e-learning: bolstering user experience and usability; endorsing continuous improvement and professional development; and stimulating interdepartmental collaboration and innovation. Despite the significant progress made by ALs, the study acknowledges the formidable challenges faced by these professionals in their capacity as DSs, specifically in areas of professional growth and evaluation. The paper presents strategic recommendations to overcome these obstacles, such as amplifying ALs' data science competencies, advocating for ongoing professional development, and endorsing the validation of their expertise through accreditation. By highlighting the essential role and proactive contributions of ALs as DSs, this study offers valuable insights and guidelines towards cultivating a robust and influential e-learning environment. Concluding with suggestions for future research, this study aims to propel the progression of academic librarianship and the enhancement of e-learning outcomes.